The price of fishmeal and the economic value added in Austral Group SAA - Ocampo Risco, Juan Carlos (2021)
Objective: Determine the relationship between the price of fishmeal and the economic added value in Austral Group SAA. Methods: It was based on a model that uses a non-experimental longitudinal exploratory approach, a quantitative correlational research focused on a representative company. Results: Regarding the price of flour and the added economic value, there is a negative relationship between both variables with a high level of significance for the price (p <10%), other significant variables are capital investment and the level of capture but with a positive relationship. Conclusions: The price of flour is a component of the value of exports, but also of the costs of Austral Group SAA and other companies in the sector. A higher price of flour raises labor costs and fishing rights, these payments should be reformulated to reduce the negative relationship.